Use of cannula ileostomy to protect a low colorectal anastomosis in patients having preoperative neoadjuvant chemoradiotherapy. (March 2014) - Hanju, H.; Jiahe, X.; Caizhao, L.; Sen, L.; Jianjiang, L.
Abstract Aim This study evaluated the efficacy and safety of ileal diversion, using a tracheal cannula, to protect from a low colorectal anastomosis in patients treated with neoadjuvant chemoradiotherapy. Method Fifty patients who presented with rectal cancer and who had accepted neoadjuvant chemoradiotherapy were included. All underwent a low anterior resection with ileal diversion by either tracheal cannula ileostomy (n = 28) or conventional loop ileostomy (n = 22). Demographics, clinical features and operation data were recorded. Results Two patients developed anastomotic dehiscence after completion of the cannula ileostomy but neither patient required any further operation. There was no difference in anastomotic dehiscence, peritonitis or requirement for further surgery in patients treated with cannula ileostomy and loop ileostomy. Conclusion Cannula ileostomy is a safe, quick, effective and convenient means of intestinal diversion after low anterior resection. Its obvious advantage over loop ileostomy is a reduced overall hospital stay and avoidance of the need to close the stoma.